A practical oxidative C–H functionalization of N-carbamoyl tetrahydro-β-carbolines with diverse potassium trifluoroborates. Issue 39 (19th September 2016) - Sun, Yi; Wang, Gang; Chen, Jiayu; Liu, Chang; Cai, Manqi; Zhu, Rongxiu; Huang, Haofei; Li, Wei; Liu, Lei
Abstract : A practical and mild metal-free oxidative C–H functionalization of N -carbamoyl tetrahydro-β-carbolines with diverse potassium trifluoroborates has been reported. Abstract : A practical and mild metal-free oxidative C–H functionalization of N -carbamoyl tetrahydro-β-carbolines has been reported. This reaction has excellent functional group tolerance, and exhibits a broad range of potassium trifluoroborate components, allowing for the facile C–H functionalization of electronically varied N -carbamoyl THCs in high efficiency with excellent regioselectivity.